Therapeutic developments for neurodegenerative GM1 gangliosidosis - Foster, Dorian; Williams, Lucian; Arnold, Noah; Larsen, Jessica (Frontiers in Neuroscience, 2024)
GM1 gangliosidosis (GM1) is a rare but fatal neurodegenerative disease caused by dysfunction or lack of production of lysosomal enzyme, β-galactosidase, leading to accumulation of substrates. The most promising treatments for GM1, include enzyme replacement therapy (ERT), substrate reduction therapy (SRT), stem cell therapy and gene editing. However, effectiveness is limited for neuropathic GM1 due to the restrictive nature of the blood-brain barrier (BBB). ERT and SRT alleviate substrate accumulation through exogenous supplementation over the patient's lifetime, while gene editing could be curative, fixing the causative gene, GLB1, to enable endogenous enzyme activity. Stem cell therapy can be a combination of both, with ex vivo gene editing of cells to cause the production of enzymes. These approaches require special considerations for brain delivery, which has led to novel formulations. A few therapeutic interventions have progressed to early-phase clinical trials, presenting a bright outlook for improved clinical management for GM1.